(untitled) (Bangladesh Critical Care Journal, 2017)
Cough, as a symptom by default gets the focus of a physician towards the chest ruling out the causes could be of the same. However an incessant cough causing life threatening extra pulmonary complications is a rarity. We present a case of an elderly female who presented with a cough with expectoration but ended up requiring strict hemodynamic monitoring due to a rectus sheath hematoma. Bangladesh Crit Care J September 2017; 5(2): 139-140